Kainate Receptors Mediate Synaptic Input to Transient and Sustained OFF Visual Pathways in Primate Retina - Puthussery, Theresa (Society for Neuroscience, 2014)
Visual signals are segregated into parallel pathways at the first synapse in the retina between cones and bipolar cells. Within the OFF pathways of mammals, the selective expression of AMPA or kainate-type glutamate receptors in the dendrites of different OFF-bipolar cell types is thought to contribute to formation of distinct temporal channels. AMPA receptors, with rapid recovery from desensitization, are proposed to transmit high temporal frequency signals, whereas kainate receptors (KARs) are presumed to encode lower temporal frequencies. Here we studied the glutamate receptors expressed by OFF-bipolar cells in slice preparations of macaque monkey retina, where the low (midget/parvocellular) and high-frequency (parasol/magnocellular) temporal channels are well characterized. We found that all OFF-bipolar types receive input primarily through KARs and that KAR antagonists block light-evoked input to both OFF-midget and OFF-parasol ganglion cells. KAR subunits were differentially expressed in OFF-bipolar types; the diffuse bipolar (DB) cells, DB2 and DB3b, expressed GluK1 and showed transient responses to glutamate and the KAR agonist, ATPA. In contrast, flat midget bipolar, DB1, and DB3a cells lacked GluK1 and showed relatively sustained responses. Finally, we found that the KAR accessory protein, Neto1, is expressed at the base of cone pedicles but is not colocalized with the GluK1 subunit. In summary, the results indicate that transient signaling in the OFF pathway of macaques is not dependent on AMPA receptors and that heterogeneity of KARs and accessory proteins may contribute to the formation of parallel temporal channels.